2011
DOI: 10.5489/cuaj.10136
|View full text |Cite
|
Sign up to set email alerts
|

The role of resection of pulmonary metastases from prostate cancer: a case report and literature review

Abstract: We report a case of a 53-year-old man who presented with two nodules in the lower lobe and one nodule in the upper lobe of the right lung almost 7 years after radical prostatectomy for pT3aN0M0, Gleason 4+5 disease, without evidence of osseous or lymphatic spread. Surgical resection of the lower lung nodules confirmed metastases, but prostate-specific antigen did not drop to undetectable levels. Isolated pulmonary metastases from prostate cancer are rare with only 33 previously described cases in the English-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…However, the significance of this finding might vary depending on the specific clinical scenario. For some patient groups, the detection rate of the contrast-enhanced VIBE sequence might be sufficient, for example, in prostate cancer patients with early biochemical relapse, because in this group lung metastases are rare and when present usually they are larger than 1 cm (26). Also many patients might already present with diagnostic CT images including the chest before undergoing the PET/MR examination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significance of this finding might vary depending on the specific clinical scenario. For some patient groups, the detection rate of the contrast-enhanced VIBE sequence might be sufficient, for example, in prostate cancer patients with early biochemical relapse, because in this group lung metastases are rare and when present usually they are larger than 1 cm (26). Also many patients might already present with diagnostic CT images including the chest before undergoing the PET/MR examination.…”
Section: Discussionmentioning
confidence: 99%
“…Wallis and colleagues, in their recent literature review, found a total of only 18 cases of solitary metastatic Pca to lung and 15 cases of multiple metastases without osseous or lymphatic involvement (2). Until now, androgen deprivation therapy (ADT) is the cornerstone of treatment for PCa patients diagnosed with metastatic progression following primary treatment, although the optimal timing and schedule of ADT is still under debate in this setting (3).…”
Section: Discussionmentioning
confidence: 99%
“…3 In a clinical study of 1290 patients diagnosed with prostate cancer, 48 patients had lung metastases, with only 11 patients (0.86%) having solitary nodule. 4 There have been several reports of isolated multiple pulmonary metastases; 5 however, none have reported lung metastases of prostate cancer and primary lung cancer detected at the same time. Our case is the first to present these unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Both surgical excision and androgen-deprivation therapy have resulted in some regression or resolution of pulmonary nodules. 5 It was reported, in a case report, that the resection of a solitary lung metastasis of prostate cancer resulted in 12 years of biochemical remission without additional therapy. 6 These findings suggest that although lung metastases are usually regarded as a manifestation of systemic disease, their early removal may be a management option for prostate cancer patients with pulmonary nodules.…”
Section: A B C D E Fmentioning
confidence: 99%